A quantitative analysis of MDMA seized at New South Wales music festivals over the 2019/2020 season: Form, purity, dose and adulterants. (16th December 2021) - O'Reilly, Matthew J. A.; Harvey, Christine A.; Auld, Robin; Cretikos, Michelle; Francis, Catherine; Todd, Stephanie; Barry, Daniel; Cullinan, Una; Symonds, Michael
Abstract: Introduction: This research aims to understand the content and nature, and to explore the harm potential, of suspected 3, 4‐methylenedioxymethamphetamine (MDMA) substances circulating at music festivals in New South Wales. Methods: Across 19 music festivals held between October 2019 and March 2020, 302 substances detected and suspected by police to contain MDMA were selected for quantitative analysis. Results: Five percent of substances contained a drug other than MDMA ( n  = 13) or no drug ( n  = 2). The remaining 95.0% ( n  = 287) contained MDMA. Of this sub‐sample, capsule was the commonest form (83.3%), followed by tablet (7.7%), crystal (6.3%) and powder (2.8%). The median MDMA base‐purity of non‐tablet forms ranged between 73.5% and 75.0%. The median MDMA base‐dose per tablet (116 mg) was higher than per capsule (68 mg). The dose range varied substantially for capsules (14–146 mg) and tablets (24–201 mg). A higher dose (130 mg or greater) was found in 3.5% of MDMA tablets or capsules. Adulterants were identified in 14.1% of MDMA substances but only 1.6% contained a psychoactive adulterant and none presented as dangerous due to their nature or low concentration. Discussion and Conclusions: Dangerous MDMA adulterants or new psychoactive substances in tablet, capsule, powder or crystal forms (whether misrepresented as MDMA or not) were unlikely to be in circulation during the study period. Harm reduction messaging should inform that a key risk‐factor for MDMA‐related harm is the high and wide variation of purity and dose across forms. Market changes may have occurred since COVID‐19, but continued monitoring will ensure messaging remains current.